Olfactory attributes and colors associated with naturalness. (June 2022) - Dantec, M.; Allain, H.; Yvert, N.; Sigrist, J.; Bensafi, M.; Lafraire, J.
Highlights: Specific olfactory properties like freshness and lightness were founded to be associated with natural odor. Green, white and yellow were reliably associated with natural products. Culture and product categories appeared to modulate associations between colors and natural products and expected intensity of natural products' odor and color. Abstract: In developed countries, naturalness is an important food attribute for the majority of consumers. However, the relation between natural products and their sensory properties are still poorly understood, and only few studies explored the olfactory attributes and colors associated with naturalness. In the present study, American and French participants were asked to associate attributes with natural and unnatural odors, and colors with natural products. Results showed that freshness was more often associated with natural odors, while green, white and yellow were the colors associated with natural products. However, our results also underline disparities between countries and categories of products, as American participants expected higher intensity of natural products' color and odor, and chose less often white than French respondents. Brown, green, and orange were more associated with food, while blue and white were chosen more often for non-foods products. Taken together, these findings bring new insights on consumers' expectations and consumers' associations between olfactory properties, colors and natural products.